2014
DOI: 10.1186/1471-2458-14-1109
|View full text |Cite
|
Sign up to set email alerts
|

Medical planning for mass-participation running events: a 3-year review of a half-marathon in Singapore

Abstract: BackgroundSystematically planning appropriate medical coverage for mass-participation running events is a challenge that has received relatively little attention in the medical literature, despite its potentially severe consequences. In particular, the literature lacks quantitative information on running events that medical planners can utilize for decisions on medical resource allocation and deployment.MethodsUsing a case-study approach, this study provides a detailed quantitative medical services utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 11 publications
4
27
2
Order By: Relevance
“…However, given that there is also a 2:1 ration male/female of starting runners, the risk of severe collapse was similar between males and females. This is in contrast to previous studies that have reported higher overall incidence of medical complications for female runners [16, 17]. However, it should be noted that whilst there is an overall 2:1 male/female ratio at Gothenburg half-marathon, this ratio varies considerably between different age groups.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…However, given that there is also a 2:1 ration male/female of starting runners, the risk of severe collapse was similar between males and females. This is in contrast to previous studies that have reported higher overall incidence of medical complications for female runners [16, 17]. However, it should be noted that whilst there is an overall 2:1 male/female ratio at Gothenburg half-marathon, this ratio varies considerably between different age groups.…”
Section: Discussioncontrasting
confidence: 91%
“…In terms of risk factors for medical complications, inexperienced runners in long distance races [14, 15] and older female runners in half-marathons have been shown to be at highest risk [16]. In a study from Singapore half-marathon, Tan et al showed that young runners as well as female runners were at a higher risk of needing medical care [17]. The risk of the sudden cardiac arrests during marathon running, however, is generally low (approximated 1/50 000 participants) [18].…”
Section: Introductionmentioning
confidence: 99%
“…While mass participation sporting events are increasingly held in many parts of the world, there have been few reports of casualty data and medical support plans. Medical planners could utilize data from similar events as a useful guide for training and equipping their staff 3 . Moreover, lessons learned can significantly reduce casualties in subsequent events by enabling preventive measures and improving preparedness 4 , 5 .…”
Section: Discussionmentioning
confidence: 99%
“…While the number of mass participation sporting events is on the rise, injury data and availability of medical support plans for such events remain underreported 3 . An understanding of the temporal and spatial characteristics of injuries sustained during triathlon races would facilitate appropriate medical support planning 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of dehydration through increasing awareness to drink required cooperation from all related stakeholders such as athletes, coaches, training center managers, and sport competition organizers. 14,24,25 This study also showed that majority of the subjects received information about hydration from television(52%, n = 11) and internet (43%, n = 9). This phenomenon was easily understood, since some TV commercials showed products for hydration and access of internet are easily get nowadays and commonly used.In the developed countries, the number of internet users reaches 86% of youth and 72% of themuse the internet to get the information about health.…”
Section: Discussionmentioning
confidence: 65%